Parliamentary and nomenclature in political life of district. Referendum, election of members of the Federation Council and deputies of the State Duma in Bolsheukovsky district of Omsk region. 1993–2011 - M. S. Novikov (Омский научный вестник: Серия "Общество. История. Современность")
Important components of Russia’s political life in this period were the referendum on the Constitution and the election of deputies of the country’s legislative bodies. In Bolsheukovsky district, federal and regional mass media influence the regional, social and political organizations acting on the ground to express their will. There is identified the degree of the influence of all types that may occur, if this occurs. The study makes it possible to raise the question of the forms of influence of power structures on the views of voters, changes in relations depending on the adjustment of the socioeconomic course and political rhetoric